15. ANALISIS KEBIJAKAN PEMERINTAH AMERIKA SERIKAT ERA PRESIDEN BARACK OBAMA TERHADAP PRAKTIK FORCED LABOUR DI INDUSTRI PERIKANAN THAILAND 2009-2014 - Abdurrasyid, Muhammad Naufal; Utomo, Tri Cahyo; P, Shary Charlotte (Journal of International Relations, 2016)
Thailand is the third largest fishery products exporter to the United States. There are twoThailand's fishery products that has a large proportion of the United States imports, cannedtuna controls 51% of the total imports and shrimp with 11%. Both products are the type offish that is most widely consumed in the United States. Behind the magnitude of Thailand'srole in the supply of fisheries products to the United States there is a fact that most of theseproducts are produced through forced labor practices. Under its domestic law, namely Section307 of the Smoot-Hawley Tariff Act of 1930 the government prohibited to import productsproduced by forced labor, however the US government ignores the law and keeping theimport policy towards Thailand. This study tries to analyze the policy by using descriptiveanalytical research. Based on wide range data related to the supply and consumption offishery products in the United States along with realism theory argument about policy makingthat prioritize self-interest, this study found that US government policy to ignores theirnational law and keeping the import policy towards Thailand was influenced by their nationalinterest to ensure food security for its people.